New perspectives on rare connective tissue calcifying diseases. (June 2016) - Rashdan, Nabil A; Rutsch, Frank; Kempf, Hervé; Váradi, András; Lefthériotis, Georges; MacRae, Vicky E
Highlights: Multifactorial mechanisms underpin connective tissue calcifying diseases (CTCs). CTCs complicate several acquired and inherited diseases. There are limited treatment options for CTCs. Studying rare CTCs helps elucidate mechanisms of common disorders. Pyrophosphate imbalance underpins connective tissue calcification in PXE and GACI. Abstract : Connective tissue calcifying diseases (CTCs) are characterized by abnormal calcium deposition in connective tissues. CTCs are caused by multiple factors including chronic diseases (Type II diabetes mellitus, chronic kidney disease), the use of pharmaceuticals (e.g. warfarin, glucocorticoids) and inherited rare genetic diseases such as pseudoxanthoma elasticum (PXE), generalized arterial calcification in infancy (GACI) and Keutel syndrome (KTLS). This review explores our current knowledge of these rare inherited CTCs, and highlights the most promising avenues for pharmaceutical intervention. Advancing our understanding of rare inherited forms of CTC is not only essential for the development of therapeutic strategies for patients suffering from these diseases, but also fundamental to delineating the mechanisms underpinning acquired chronic forms of CTC.